EKSISTENSI HUKUM WARIS DI INDONESIA: ANTARA ADAT DAN SYARIAT - Komari Komari (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2016)
This paper explains about the application of inheritance law in Indonesia which is strongly influenced by three law systems such as Islamic law, customary law, and Western law. At the beginning of Islam in Indonesia, Islamic law is very dominant in the implementation of Islamic inheritance law which is intergrated with culture and tradition among Muslim society. In Colonial period, the government of Dutch East Hindia started to establish Western law for European and East Asian people. But for the Muslim citizens in Indonesia was implementting the combination of Islamic law and customary law. In the independence period, the political of law has been changed through unification and codification of Islamic law into the Indonesia rules formally, including in the application of Islamic inheritance law. As long as this policy, Islamic inheritance law in Indonesia has a characteristic of the combination between Islamic law and customary law.